2007
DOI: 10.1016/j.trstmh.2006.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of Phlebotomus (Larroussius) langeroni (Diptera: Psychodidae) with Leishmania infantum in Tunisia

Abstract: Phlebotomine sand flies were captured from an active transmission focus of sporadic cutaneous leishmaniasis, caused by Leishmania infantum, in El Kef region, northern Tunisia. Both Phlebotomus perniciosus and P. langeroni were found. Phlebotomus langeroni females showed a statistically significant intradomiciliary dominance (P<0.01 for the 2003 and 2004 seasons) when compared to animal shelters. During the 2003 season, dissection of collected female specimens showed the presence of flagellates within the diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This knowledge greatly benefited of the availability of techniques used in typing isolates obtained from humans or from reservoirs and sandflies. In this respect, IEE or molecular techniques allowed a more precise identification of the Leishmania at the species, zymodeme and genomic (schizodeme) level (Ben Hammouda et al, 2000;Ben Said et al, 2006;Guerbouj et al, 2007;Guizani et al, 1993Guizani et al, , 1994aGuizani et al, , 1994bGuizani et al, 2002;Hanafi et al, 2001;Kallel et al, 2008b). As far as zymodemes are concerned, it was shown that L. major was much more homogeneous than L. infantum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This knowledge greatly benefited of the availability of techniques used in typing isolates obtained from humans or from reservoirs and sandflies. In this respect, IEE or molecular techniques allowed a more precise identification of the Leishmania at the species, zymodeme and genomic (schizodeme) level (Ben Hammouda et al, 2000;Ben Said et al, 2006;Guerbouj et al, 2007;Guizani et al, 1993Guizani et al, , 1994aGuizani et al, , 1994bGuizani et al, 2002;Hanafi et al, 2001;Kallel et al, 2008b). As far as zymodemes are concerned, it was shown that L. major was much more homogeneous than L. infantum.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the emergent character of Kairouan foci which may favour and select atypical or rare variants (Aoun et al, 2008;Ben Abda et al, 2009). Involvement of different www.intechopen.com sandfly species in transmission of different L. infantum parasites can not be excluded (Guerbouj et al 2007). It is well established that different sandfly species belonging to the sub-genus Larroussius are involved in the transmission of L. infantum; in Tunisia clear association between sandfly species and bioclimate was demonstrated and presence of species of this subgenus in the different bioclimatic zones allowed explaining the extension of VL (Zhioua et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, no L. infantum strain has been isolated from this phlebotomine sand fly species yet. Also, L. infantum DNA was detected from a P. langeroni, P. longicuspis, P. perfiliewi, P. papatasi, and Sergentomyia minuta using molecular tools [45,46]. However, neither parasite isolation from these sand flies species nor L. infantum isoenzymatic identification were carried out in Tunisia yet to confirm their role as vector of L. infantum taxon.…”
Section: Transmission Cyclementioning
confidence: 98%